Analisis Kesulitan Belajar pada Mata Pelajaran Matematika selama Pembelajaran Tatap Muka (PTM) - Siti Wardah; Ahmad Syarifuddin; Amir Hamzah; Tutut Handayani; Ines Tasya Jadiddah (IBTIDA, 2022)
This study aims to describe the results of research regarding: (1) The process of learning mathematics during Face-to-face Learning (PTM); The difficulties faced by students in learning mathematics during Face-to-face Learning (PTM); (3) Solutions to overcome students’ mathematics learning difficulties during Face-to-face Learning (PTM). This study uses a descriptive qualitative research type by directly examining the field. The subjects of this research are teachers, and students of lass VI. Data collection techniques by observation, interviews, and documentation. Based on the data analysis that has been carried out, the results of the research show the following: first, the process of implementing PTM learning in mathematics subjects, it can be seen that the teacher when entering the classroom to start learning does not use any media except the teaching material book and learning methods explain on the blackboard so that it is not effective and makes students bored. Second, the learning difficulties faced by students during PTM in mathematics are difficulty understanding concepts, difficulty in counting, and difficulty solving problems. Third, efforts to overcome difficulties in learning mathematics during PTM are by using concrete learning media, increasing practice questions, and cooperating with parents.